2003
DOI: 10.1063/1.1537512
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic actuation by modulation of surface stresses

Abstract: We demonstrate the active manipulation of nanoliter liquid samples on the surface of a glass or silicon substrate by combining chemical surface patterning with electronically addressable microheater arrays. Hydrophilic lanes designate the possible routes for liquid migration while activation of specific heater elements determines the trajectories. The induced temperature fields spatially modulate the liquid surface tension thereby providing electronic control over the direction, timing, and flow rate of contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
148
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 165 publications
(148 citation statements)
references
References 19 publications
0
148
0
Order By: Relevance
“…All other regions of the chip surface were chemically treated to repel the liquids tested. 8,10 As shown in Fig. 4(b), the presence of three distinct glycerol droplets of slightly different volume locally increased the capacitive signal along the linear array of electrodes (w = 800 mm).…”
Section: B Droplet Position Sensormentioning
confidence: 84%
“…All other regions of the chip surface were chemically treated to repel the liquids tested. 8,10 As shown in Fig. 4(b), the presence of three distinct glycerol droplets of slightly different volume locally increased the capacitive signal along the linear array of electrodes (w = 800 mm).…”
Section: B Droplet Position Sensormentioning
confidence: 84%
“…The approaches described in this work address many of the fluid-handling challenges that are faced when working with microfluidic devices [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] including those involving laminar flow, 22,38 droplets, 21,[39][40][41] and cell culture experiments. [42][43][44] The simplicity of this pumping method overall and the use of the guiding structures make it robust to differences in pushing/pulling force; the user simply places a sample at the inlet and then pushes/pulls the pumping lid to generate the flow.…”
Section: Discussionmentioning
confidence: 99%
“…Methods within this category include electrowetting, 5,6 dielectrophoresis, 7,8 surface-acoustic waves 9 and thermocapillary propulsion. 10 With each of these techniques, discrete droplets can be transported along a planar substrate by activation of embedded electrodes or microheaters.…”
Section: Introductionmentioning
confidence: 99%
“…It does not occur in the symmetric splitting of long liquid filaments, where the liquid filament thickness above the resistor decreases monotonically. 48 In geometric terms, detachment of a droplet requires a sufficiently high temperature gradient such that the leading edge of the cell meniscus recedes to the left of the center of R 1 . For the device layouts used in this study, this situation corresponds to a leading edge position x apex # 400 mm, as indicated by the white dashed line in Fig.…”
mentioning
confidence: 99%